Effect of far-infrared radiation on perineal wound pain and sexual function in primiparous women undergoing an episiotomy - Li-Hua Huang; Yu-Fen Lai; Gin-Den Chen; Maw-Sheng Lee; Soo-Cheen Ng (Elsevier, 2019)
Objective: To evaluate the effect of far-infrared radiation on postpartum perineal pain and sexual function in primiparous women undergoing an episiotomy and 2nd degree perineal laceration. Materials and methods: From May 2016 to May 2017, primiparous women with term pregnancies and vaginal deliveries with an episiotomy due to obstetric indications and 2nd degree perineal lacerations were invited to participate in this study. Women were randomly assigned into a far-infrared (FIR) group and a control group. Visual Analogue Scale (VAS) was used to evaluate the perineal pain immediately postpartum, and at 1 week and 6 weeks postpartum. Pelvic Organ Prolapse Urinary Incontinence Sexual Questionnaire (PISQ-12) was used to evaluate sexual function at 6 weeks, 3 months and 6 months postpartum. Results: The data of the control group (n = 22) and FIR group (n = 18) were analyzed. Most of the women had minor perineal pain one week after delivery (1.1 ± 0.9 in control group vs 1.4 ± 1.5 in FIR group) and there was no significant difference between groups. The FIR group had a higher PISQ-12 total score at 3 months (35.4 ± 6.4 vs 34.7 ± 5.7) and 6 months (36.4 ± 5.6 vs 35.6 ± 5.7) postpartum compared with the control group but there was no statistically significant difference. Conclusion: Our study did not show any additional benefit of postpartum far-infrared radiation on primiparous women undergoing an episiotomy and 2nd degree perineal lacerations. Keywords: Far-infrared radiation, Episiotomy, Perineal pain, Sexual function